Hydrophobically modified poly(acrylic acid) using 3-pentadecylcyclohexylamine: synthesis and rheology - Shedge, A. S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique; Pcrrin, P.; Chassenieux, Christophe; Badiger, Manohar V. (Macromolecular Chemistry and Physics, 2005)
Hydrophobically modified poly(acrylic acid) was synthesized using 3-pentadecylcyclohexylamine (3-PDCA), which was in turn synthesized from 3-pentadecylphenol, one of the components of cashew-nut shell liquid (CNSL), a renewable resource material. H-1 NMR spectra confirmed the incorporation of 3-PDCA onto PAA and a series of HMPs with three different molar concentrations, viz. congruent to 3, 5 and 7 mol-% of 3-PDCA, were synthesized. An increase in viscosity with increasing hydrophobic content was observed by rheological measurements. The critical association concentrations were determined using an Ubbelohde viscometer and a controlled stress rheometer. The stability of HMPs towards temperature and shear was studied. Rheological measurements showed that there was a steady increase in viscosity with increase in hydrophobe content due to the formation of reversible networks. These polymers exhibited gel-like behavior at low concentrations (greater than or equal to2 wt.-%) with an apparent yield stress (ca. 10 Pa) and showed shear thinning properties (non-Newtonian). However, below a critical concentration, c [eta], they showed Newtonian behavior.
Keywords: 3-pentadecylcyclohexylamine (3-PDCA); hydrophobically modified polymers (HMPs); poly(acrylic acid); reversible associations; Rheology

Flexible ring polymers in an obstacle environment: Molecular theory of linear viscoelasticity - Iyer, Balaji V. S.; Lele, Ashish K.; Juvekar, Vinay A. (Physical Review E, 2006)
We formulate a coarse-grained mean-field approach to study the dynamics of the flexible ring polymer in any given obstacle (gel or melt) environment. The similarity of the static structure of the ring polymer with that of the ideal randomly branched polymer is exploited in formulating the dynamical model using aspects of the pom-pom model for branched polymers. The topological constraints are handled via the tube model framework. Based on our formulation we obtain expressions for diffusion coefficient D, relaxation times tau, and dynamic structure factor g(k,t). Further, based on the framework we develop a molecular theory of linear viscoelasticity for ring polymers in a given obstacle environment and derive the expression for the relaxation modulus G(t). The predictions of the theoretical model are in agreement with previously proposed scaling arguments and in qualitative agreement with the available experimental results for the melt of rings.

Nanocomposites of polypropylene impact copolymer and organoclays: role of compatibilizers - Deenadayalan, E.; Vidhate, Shailesh; Lele, Ashish K. (Polymer International, 2006)
Nanocomposites of polypropylene impact copolymer and organoclays were prepared using different compatibilizers (polypropylene-graft-(maleic anhydride) (PPMA), polyethylene-graft-(maleic anhydride) (PEMA) and their mixture) and varying percentages of clay (3 and 6%) in an attempt to obtain balanced mechanical properties. The nanocomposites were prepared by melt compounding and test specimens were prepared by injection molding. Mechanical properties such as tensile, flexural and Izod impact strength are reported. The clay dispersion was investigated using wide-angle X-ray diffraction while the phase morphology was characterized using scanning electron microscopy. It is shown that the mechanical properties of the system with mixed PPMA and PEMA compatibilizers showed the best balance of mechanical properties among the nanocomposites explored. (C) 2006 Society of Chemical Industry.
Keywords: clay; compatibilizers; Nanocomposites; polypropylene

Studies on shrikhand rheology - Kulkarni, C.; Belsare, N.; Lele, Ashish K. (Journal of Food Engineering, 2006)
Shrikhand, a popular Indian dessert made from yogurt, is manufactured on an industrial scale using several chemical engineering unit operations such as mixing, filtration and heat transfer. Understanding the rheology of shrikhand is not only relevant for designing large scale mixers but can also provide quantitative means for linking the microstructure of shrikhand to its perception of texture, consistency and taste. We show here that shrikhand exhibits a combination of several rheological properties such as weak gel-like viscoelasticity, an apparent yield stress, thixotropy and long structural recovery time scales. For instance, the elastic modulus is always higher than the loss modulus over the measurable frequency range and that both moduli show only weak frequency dependence that is a characteristic of gel-like consistency. Forward and reverse rate sweep tests show a distinct hysteresis loop, which is a signature of thixotropic character. In an attempt to trace the origins of these rheological properties in shrikhand we characterized its microstructure and showed that there exist two different microstructures: one composed of crystallites of milk fats having a length scale of similar to 50-100 mu m, and the other composed of aggregates of colloidal cascin micelles of similar to 0.5-10 mu m size. Our studies show that while the temperature sensitivity of the viscoelastic parameters is dominated by the semicrystalline milk fat microstructure, the shear sensitivity is largely dictated by the protein network. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Microstructure; Rheology; shrikhand

Synthesis and characterization of novel hydrophobically end-capped poly(ethylene oxide)s [PEOs] - Badiger, Manohar V.; Kadam, Vijay S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique (Macromolecular Symposia, 2006)
We report on the synthesis and characterization of a novel hydrophobically modified end-capped poly(ethylene oxide)s. The end-capping agent of this polymer was designed and synthesised from a renewable resource material namely, gallic acid (i.e. 3,4,5-trihydroxybenzoic acid), the byproduct of tannin industry. The hydroxyl groups at 3, 4 and 5 positions of gallic acid provide an opportunity for varying the hydrophobicity of the compound. The hydrophobic end-capping compound, 3,4,5tridodecyloxy bezoylazide was prepared from gallic acid and PEGS with different chain lengths (of number average molecular weights, 10000 and 35000 g/mol) were endcapped. using 3,4,5-tridodecyloxybenzoyl azide. The quantitative analysis of end-capping in the polymers was demonstrated by H-1-NMR spectroscopy and the rheological studies were carried out in the surfactant solutions.
Keywords: end-capped PEOs; hydrophobically modified polymers; water-soluble polymers

Geometrical solution to the sharkskin instability - Pol, Harshawardhan V.; Joshi, Yogesh M.; Tapadia, Prashant S.; Lele, Ashish K.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2007)
We study the effect of die exit divergence on the sharkskin behavior, both experimentally as well as through the use of computational fluid dynamics (CFD) simulations. Sharkskin or surface fracture is known to occur immediately after the die exit, because of the large elongational deformation that a polymer melt experiences as it exits the die. We show that the diverging taper at the die exit postpones or completely removes the occurrence of sharkskin. The corresponding CFD simulations of an equivalent K-BKZ fluid show that the taper at the die exit significantly reduces the severity of the elongational flow, thereby reducing the normal stresses as the polymer melt leaves the die. We believe that, in an extrusion operation, the provision of a diverging taper at the die exit is one of the potential measures by which sharkskin instability can be eliminated on an industrial scale.

Simulation of viscoelastic flows of polymer solutions in abrupt contractions using an arbitrary lagrangian eulerian (ALE) based finite element method - Ganvir, Vivek; Lele, Ashish K.; Thaokar, Rochish; Gautham, Basavarsu P. (Journal of Non-Newtonian Fluid Mechanics, 2007)
We present a method for simulation of viscoelastic flows using an Arbitrary Lagrangian Eulerian (ALE) technique based finite element formulation. The ALE technique provides advantages of both Lagrangian and Eulerian frameworks by allowing the computational mesh to move in an arbitrary manner, independent of the material motion. In the present method, a fractional step ALE technique is employed in which the Lagrangian phase of material motion and convection arising out of mesh motion are decoupled. In the first step the relevant flow and constitutive equations are solved in Lagrangian framework. The simpler representation of polymer constitutive equations in a Lagrangian framework avoids the difficulties associated with convective terms thereby resulting in a robust numerical formulation. In the second step the mesh is moved in ALE mode and the associated convection of the stress is performed using a Godunov type scheme. This ALE technique is easy to implement and can accurately simulate the complex viscoelastic behaviour of transient polymer flow through complex geometries. In the present study, steady flows through abrupt contractions of planar and axisymmetric geometries are studied by performing transient flow simulations until steady state is achieved. The proposed method is validated with previously published numerical and experimental studies for polymer solutions obeying the Oldroyd B and Phan Thien Tanner (PTT) models. The simulated corner and lip vortex enhancement mechanism and flow behavior are in good agreement with experimentally obtained flow visualization photographs. The strength of the proposed method lies in its ability to simulate free surface flows such as swell. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: abrupt contraction; Arbitrary Lagrangian Eulerian; finite element; simulations

Blob-spring model for the dynamics of ring polymer in obstacle environment - Lele, Ashish K.; Iyer, Balaji V. S.; Juvekar, Vinay A. (XVTH International Congress on Rheology - the Society of Rheology 80th Annual Meeting, Pts 1 and 2, 2008)
The dynamical behavior of cyclic macromolecules in a fixed obstacle (FO) environment is very different than the behavior of linear chains in the same topological environment; while the latter relax by a snake-like reptational motion from their chain ends(1) the former can relax only by contour length fluctuations since they are endless.(2) Duke, Obukhov and Rubinstein proposed a scaling model (the DOR model) to interpret the dynamical scaling exponents shown by Monte Carlo simulations of rings in a FO environment.(2) We present a model (blob-spring model) to describe the dynamics of flexible and non-concatenated ring polymer in FO environment based on a theoretical formulation developed for the dynamics of an unentangled fractal polymer.(3) We argue that the perpetual evolution of ring perimeter by the motion of contour segments results in an extra frictional load. Our model predicts self-similar dynamics with scaling exponents for the molecular weight dependence of diffusion coefficient and relaxation times that are in agreement with the scaling model proposed by Obukhov et al.(2).
Keywords: fractal polymer dynamics; linear viscoelasticity; ring polymer dynamics

Gelation of regenerated fibroin solution - Nagarkara, Shailesh; Lele, Ashish K.; Chassenieux, Christophe; Nicolai, Taco; Durand, Dominique (15th International Congress on Rheology/80th Annual Meeting of the Society-of-Rheology, 2008)
Silk fibroin is a high molecular weight multiblock ampiphillic protein known for its ability to form high strength fibers. It is also biocompatible; silk sutures have been traditionally used for many centuries. Recently, there has been much interest in making silk hydrogels for applications ranging from tissue engineering to controlled delivery. Fibroin gels can be formed from aqueous solutions by changing one or more state variables such as pH, temperature and ionic strength. In this work we present our investigations on the gelation of aqueous fibroin solutions derived from Bombyx Mori silk using light scattering, confocal microscopy and rheological techniques.
Keywords: dynamic light scattering; Rheology; silk fibroin gel

Self-diffusion coefficient of ring polymers in semidilute solution - Iyer, Balaj V. S.; Shanbhag, Sachin; Juvekar, Vinay A.; Lele, Ashish K. (Journal of Polymer Science Part B-Polymer Physics, 2008)
In a topologically constraining environment the size of a flexible nonconcatenated ring polymer (macrocycles) and its dynamics are known to differ from that of linear polymers. Hence, the diffusion coefficient of ring polymers can be expected to be different from linear chains. We present here scaling arguments for the concentration and molecular weight dependence of self-diffusion coefficient of ring polymers in semidilute solutions, and show that contrary to expectations these scaling relations are identical to what is known for linear polymers. At higher concentrations excluded volume interactions arising from possibilities of segmental overlap can become effective for large ring polymers. In this regime the diffusion coefficient of large ring polymers shows a relatively weaker dependence on concentration and molecular weight. (C) 2008 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 46: 2370-2379, 2008
Keywords: Diffusion; Macrocycles; Monte Carlo simulation

Prediction of extrudate swell in polymer melt extrusion using an Arbitrary Lagrangian Eulerian (ALE) based finite element method - Ganvir, Vivek; Lele, Ashish K.; Thaokar, Rochish; Gautham, Basavarsu P. (Journal of Non-Newtonian Fluid Mechanics, 2009)
Accurate prediction of extrudate (die) swell in polymer melt extrusion is important as this helps in appropriate die design for profile extrusion applications. Extrudate swell prediction has shown significant difficulties due to two key reasons. The first is the appropriate representation of the constitutive behavior of the polymer melt. The second is regarding the simulation of the free surface, which requires special techniques in the traditionally used Eulerian framework. In this paper we propose a method for simulation of extrudate swell using an Arbitrary Lagrangian Eulerian (ALE) technique based finite element formulation. The ALE technique provides advantages of both Lagrangian and Eulerian frameworks by allowing the computational mesh to move in an arbitrary manner, independent of the material motion. In the present method, a fractional-step ALE technique is employed in which the Lagrangian phase of material motion and convection arising out of mesh motion are decoupled. In the first step, the relevant flow and constitutive equations are solved in Lagrangian framework. The simpler representation of polymer constitutive equations in a Lagrangian framework avoids the difficulties associated with convective terms thereby resulting in a robust numerical formulation besides allowing for natural evolution of the free surface with the flow. In the second step, mesh is moved in ALE mode and the associated convection of the variables due to relative motion of the mesh is performed using a Godunov type scheme. While the mesh is fixed in space in the die region, the nodal points of the mesh on the extrudate free surface are allowed to move normal to flow direction with special rules to facilitate the simulation of swell. A differential exponential Phan Thien Tanner (PTT) model is used to represent the constitutive behavior of the melt. Using this method we simulate extrudate swell in planar and axisymmetric extrusion with abrupt contraction ahead of the die exit. This geometry allows the extrudate to have significant memory for shorter die lengths and acts as a good test for swell predictions. We demonstrate that our predictions of extrudate swell match well with reported experimental and numerical simulations. (c) 2008 Elsevier BY. All rights reserved.
Keywords: Arbitrary Lagrangian Eulerian; Extrudate (die) swell; Free surface simulations

Reactive extrusion of poly(L-Lactic Acid) with glycidol - Deenadayalan, E.; Lele, Ashish K.; Balasubramanian, M. (Journal of Applied Polymer Science, 2009)
Glycidol modified polylactic acid (PLLA) polymers have been prepared by reactive extrusion. Influences of residence time and the concentration of glycidol on the extent of reaction with different weight average molecular weight (45,000, 65,000, and 100,000) PLLA's were studied. Structure-property relationship has been established by measuring molecular, mesoscopic, and macroscopic properties. Under reactive extrusion conditions glycidol reacted with the end groups of PLLA to initiate chain extension. Low-molecular weight PLLA reacted with glycidol faster than the medium molecular weight PLLA, whereas high-molecular weight PLLA did not show significant reactions. The glass transition temperature, melting temperature, crystallization temperature, and heat of fusion were measured for unmodified and modified PLLA's. Chain extended PLLA had higher T(g) and T(m) than the unmodified samples. Time sweep rheological experiments were performed to test the melt stability of PLLA. Chain extended PLLA's were found to retain viscoelastic properties for much longer time than the unreacted samples. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 1391-1398, 2009
Keywords: biodegradable; reactive extrusion; Rheology; structure-property relations; Thermal properties

Self-similar dynamics of a flexible ring polymer in a fixed obstacle environment: a coarse-grained molecular model - Iyer, Balaji V. S.; Lele, Ashish K.; Juvekar, Vinay A.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2009)
In this contribution we concern ourselves with an interesting problem, namely, the dynamics of ideal flexible ring polymers constrained in tin array of fixed obstacles. The fundamental issue in this problem is to understand how a topologically constrained polymer chain is able to relax its conformation in the absence of chain ends. The key physics was provided in tin elegant scaling theory by Rubinstein and co-workers (Obukhov, S. P; Rubinstein, M.; Duke, T. Dynamics of a Ring Polymer in a Gel. Phys. Rev. Lett. 1994, 73, 1263-1267). In this work we develop a coarse-grained mean-field model based oil the physical arguments of the scaling theory and derive constitutive relations for rings in fixed obstacle and melt environments. The model is composed of three distinct steps. In the first step the dynamics of an arbitrary section of a ring chain is worked out based oil fractal Blob-Spring (BS) dynamics, and the center of mass diffusion and the relaxation spectrum of this section are determined. In the second step the center of mass diffusion obtained using the BS dynamics is used to model the one-dimensional diffusion of the section in a topologically constrained environment. In the final step we invoke the idea of dynamic self-similarity and argue that the dynamics described in the first and the second step, for any arbitrary section of the chain, applies to all sections of the chain. The constitutive relation is obtained consequently as the superposition of dynamic response of all sections of the ring chain.

Some mechanistic insights into the gelation of regenerated silk fibroin sol - Nagarkar, Shailesh; Patil, Avinash; Lele, Ashish K.; Bhat, Suresh K.; Bellare, Jayesh R.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2009)
We provide some new insights into the kinetics and mechanism of sol-gel transition as it pertains to regenerated silk fibroin, which is the principle structural protein of silkworm silk fiber. Silk fibroin was dissolved in lithium bromide and dialyzed against deionized water to prepare a regenerated fibroin solution. This solution was found to be unstable at lower pH and transformed into a colloidal gel. The kinetics and mechanism of the sol-gel transition were investigated using rheology and light scattering. We show that gelation proceeds in two steps. In the first step, a weak gel is formed almost immediately upon lowering the pH, while in the second step further gelation proceeds rapidly after a long induction time to form a self-similar structure.

Synthesis of Sb-doped SnO2 nanowires and hyperbranched structures - Sathe, Bhaskar R.; Patil, Mrudula; Walke, Pravin S.; Vivek, J. P.; Lele, Ashish K.; Pillai, Vijayamohanan K.; Mulla, Imtiaz S. (Science of Advanced Materials, 2009)
Branched nanostructures of semiconducting materials are of great interest for their potential applications in optoelectronic, photonic devices and sensors. We herein describe a facile single-step chemical vapor deposition route for the synthesis of Sb-SnO2 hyperbranched nanostructures comprised of elongated nanowires with 30-40 nm diameter and 10-20 Am length. The morphology and structure has been characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), selective area electron diffraction (SAED), and powder X-ray diffraction (XRD). Also, a possible mechanism is proposed for the growth of nanowires into the hyperbranched form on the basis of the substrate effect, the role of Au nanoparticles, and the effect of Sb doping on specific morphology evolution. Interestingly, electrical conductivity measurements as a function of temperature suggest a semiconducting behavior, despite being governed by different electron-transport mechanisms with activation energies of 0.55 and 0.17 eV, which correspond to pure SnO2 and Sb-SnO2 nanowires, respectively. A precise control over the operating parameters not only envisages custom-designed, branched structures by a simple and economical route but also offers an alternative method to the expensive and tedious nanofabrication techniques for industrial applications.
Keywords: Au Nanoparticles; chemical vapor deposition; Sb-SnO2 Hyperbranched Nanostructures

Abrupt shear thickening of aqueous solutions of hydrophobically modified poly(N,N `-dimethylacrylamide-co-acrylic acid) - Lele, Ashish K.; Shedge, Aarti; Badiger, Manohar V.; Wadgaonkar, Prakash; Chassenieux, Christophe (Macromolecules, 2010)
We report some new and interesting observations on the abrupt and large shear-induced thickening of aqueous solutions of hydrophobically modified poly(N,N'-dimethylacrylamide-co-acrylic acid). High molecular weight copolymer was prepared by free radical copolymerization of N,N'-dimethylacrylamide [DMA] and acrylic acid [AA] and was subsequently modified to different extents using a hydrophobic compound, namely, 3-pentadecylcyclohexylamine [3-PDCA], which is derived from a renewable resource material, cashew nutshell liquid [CNSL]. The structural elucidation of the base copolymer and the hydrophobically modified copolymers was performed by (1)H and (13)C NMR spectroscopy. The zero shear viscosities [eta(0)] of the hydrophobically modified polymers were lower than that of the precursor poly(N,N'-dimethylacrylamide-co-acrylic acid) until some critical polymer concentration, which increased with increase in hydrophobic modification. Above the critical concentrations, the eta(0) of the hydrophobically modified copolymers surpassed that of the precursor at the same concentration. At moderate shear rates some of these hydrophobically modified copolymers exhibited an abrupt shear-induced thickening in which the viscosity of the samples increased severalfold. We show here from creep experiments that thickening occurs only when the shear rate reaches a critical value, (gamma) over dot(crit), and that the thickened samples can be trapped in different metastable states by controlling the applied stress. Interestingly, the shear thickened samples showed further thickening upon decreasing the applied stress. Eventually, the metastable samples revert to their equilibrium states at characteristic time that depends on (small) probe stress.

Hydrophobically modified poly(vinyl alcohol) using alkoxy-substituted methyl gallate: synthesis and rheology - Shedge, Aarti S.; Wadgaonkar, Prakash P.; Lele, Ashish K.; Badiger, Manohar V. (Journal of Polymer Science Part B-Polymer Physics, 2010)
Hydrophobically modified poly(vinyl alcohol) (HMPVA) polymers were synthesized by potassium t-butoxide-catalyzed reaction of PVA with methyl 3,4,5-tris(n-octyloxy) benzoate (MGC(8))/3,4,5-tris(n-dodecyloxy) benzoate (MGC(12)) and 1,3-propane sultone. The concentration of 1,3-propane sultone was kept constant at 10 mol %. and that of MGC(8) (2, 3, and 4 mol %)/MGC(12) (2 and 3 mol %) was varied to obtain HMPVAs with different hydrophobic contents. The incorporation of MGC(8)/MGC(12) and 1,3-propane sultone onto HMPVA was confirmed by NMR spectroscopy. Rheological properties of aqueous solutions also confirmed the presence of hydrophobic and charged functional groups on HMPVAs. In the semidilute regime, the specific viscosity of HMPVAs followed concentration scaling that is typical of polyelectrolytes. At higher concentrations, the HMPVA solutions with 3 and 4 mol % of MGC(8) exhibited large increase in specific viscosity. Oscillatory experiments on these solutions exhibited gel-like behavior at polymer concentrations of 40-50 g/L. Confocal microscopy images of HMPVA with 4 mol % of MGC(8) clearly indicated the existence of microgels. The tendency of formation of microgels further increased with increasing chain length of the hydrophobe, that is, with MGC(12). These samples exhibited rheological behavior that is typical of soft solids and was therefore probed by the strain-rate frequency superposition technique reported recently in the literature. HMPVAs with improved rheological properties show potential applications as thickeners in cosmetic creams, lotions and as drug carriers in pharmaceutical formulations. (C) 2010 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 48: 1054-1063, 2010
Keywords: gallic acid; hydrophobically modified poly(vinyl alcohol); Rheology; water-soluble polymers

Strain-rate frequency superposition in large-amplitude oscillatory shear - Kalelkar, Chirag; Lele, Ashish K.; Kamble, Samruddhi (Physical Review E, 2010)
In a recent work, Wyss et al. [Phys. Rev. Lett. 98, 238303 (2007)] have noted a property of ``soft solids'' under oscillatory shear, the so-called strain-rate frequency superposition. We extend this study to the case of soft solids under large-amplitude oscillatory shear (LAOS). We show results from LAOS studies in a mono-disperse hydrogel suspension, an aqueous gel, and a biopolymer suspension and show that constant strain-rate frequency sweep measurements with soft solids can be superimposed onto master curves for higher harmonic moduli with the same shift factors as for the linear viscoelastic moduli. We show that the behavior of higher harmonic moduli at low frequencies in constant strain- rate frequency sweep measurements is similar to that at large strain amplitude in strain- amplitude sweep tests. We show surface plots of the harmonic moduli and the energy dissipation rate per unit volume in LAOS for soft solids and show experimentally that the energy dissipated per unit volume depends on the first harmonic loss modulus alone, in both the linear and the nonlinear viscoelastic regime.

Structure and gelation mechanism of silk hydrogels - Nagarkar, Shailesh; Nicolai, Taco; Chassenieux, Christophe; Lele, Ashish K. (Physical Chemistry Chemical Physics, 2010)
Silk fibroin was regenerated from cocoons produced by the silkworm Bombyx Mori. Light scattering showed that an aqueous solution of the regenerated silk fibroin (RSF) was made of individual proteins with a weight average molar mass of about 4 x 10(5) g mol(-1) and a hydrodynamic radius of about 10 nm. Gel formation of RSF in acidic solutions was investigated as a function of the pH (2-4), concentration (0.5-10 g L(-1)) and temperature (5-70 degrees C). The structure of the gels was studied using light scattering and confocal laser scanning microscopy. The structure was found to be self-similar from length scales of less than 15 nm up to length scales of about 1 mm, and characterized by a correlation length of a few microns. Gel formation was tracked using turbidity, rheology, light scattering and circular dichroism. Gelation involves the formation of self-similar aggregates with a growth rate that increases exponentially. The protein aggregation is correlated to, and perhaps caused by, the formation of beta-sheets, the fraction of which also increases exponentially with time.

Extrudate swell of linear and branched polyethylenes: ALE simulations and comparison with experiments - Ganvir, Vivek; Gautham, Basavarsu P.; Pol, Harshawardhan; Bhamla, M. Saad; Sclesi, Lino; Thaokar, Rochish; Lele, Ashish K.; Mackley, Malcolm (Journal of Non-Newtonian Fluid Mechanics, 2011)
Extrudate swell is a common phenomenon observed in the polymer extrusion industry. Accurate prediction of the dimensions of an extrudate is important for appropriate design of dies for profile extrusion applications. Prediction of extrudate swell has been challenging due to (i) difficulties associated with accurate representation of the constitutive behavior of polymer melts, and (ii) difficulties associated with the simulation of free surfaces, which requires special techniques in the traditionally used Eulerian framework. In a previous work we had argued that an Arbitrary Lagrangian Eulerian (ALE) based finite element formulation may have advantages in simulating free surface deformations such as in extrudate swell. In the present work we reinforce this argument by comparing our ALE simulations with experimental data on the extrudate swell of commercial grades of linear polyethylene (LLDPE) and branched polyethylene (LOPE). Rheological behavior of the polymers was characterized in shear and uniaxial extensional deformations, and the data was modeled using either the Phan-Thien Tanner (PTT) model or the eXtended Pom-Pom (XPP) model. Additionally, flow birefringence and pressure drop measurements were done using a 10:1 contraction-expansion (CE) slit geometry in a MultiPass Rheometer. Simulated pressure drop and contours of the principal stress difference were compared with experimental data and were found to match well. This provided an independent test for the accuracy of the ALE code and the constitutive equations for simulating a processing-like flow. The polymers were extruded from long (L/D=30) and short (L/D=10) capillaries dies at 190 degrees C. ALE simulations were performed for the same extrusion conditions and the simulated extrudate swell showed good agreement with the experimental data. Crown Copyright (C) 2010 Published by Elsevier B.V. All rights reserved.
Keywords: ALE-FEM; extrudate swell; Flow birefringence; MultiPass Rheometer; PSD; PTT; XPP

Influence of carbon-based nanofillers on the melt flow singularity of linear polyethylene - Xu, Han; Lele, Ashish K.; Rastogi, Sanjay (Polymer, 2011)
A quantitative power law relationship between molecular weight and flow criticalities is uncovered that links stick-slip theory with the melt flow singularity observed during capillary flow. The singularity arises from decrease in pressure during melt flow of linear polyethylene through capillary die in a narrow temperature window. The molecular origin of the window effect is attributed to slip flow arising from disengagement of chains adsorbed to melt-wall interface from free chains in melt. Considering the similar molecular configuration of the linear polyethylene and carbon nanotubes (CNTs), the stretched chain conformation of the adsorbed chains in the presence of CNTs is influenced. The potential to broaden the window temperature interval in the presence of CNTs is explored. For the study, multi-walled carbon nanotubes (MWCNTs) are added in the linear polyethylene. The influence of the filler aspect ratio on the window effect is further investigated in the presence of carbon black (CBs). The presence of MWCNTs broadens the window temperature interval and increases the decrease in pressure. Contrary to MWCNTs in the presence of CBs the extrusion window narrows and reduction in the pressure-decrease occurs. It is also found that the two carbon nanofillers have a significant impact on flow-induced solidification. Both, the crystallisation rate and the onset temperature of crystallisation, increase with the loading of the two nanofillers. A closer comparison between the two carbon nanofillers at the same loading suggests that the crystallisation is more influenced in MWCNT-PE composites. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Capillary flow; Carbon fillers; Polyethylene

Numerical and experimental studies on extrudate swell of branched polyethylene through axisymmetric and planar dies - Ganvir, Vivek; Gautham, Basavarsu P.; Thaokar, Rochish; Lele, Ashish K.; Pol, Harshwardhan (Journal of Polymer Engineering, 2011)
Extrudate swell is simulated using an Arbitrary Lagrangian Eulerian (ALE) technique based finite element formulation and the same has been validated by comparing the results with reported numerical and experimental studies. In the present work we compare our ALE simulations with our own experimental data on the extrudate swell of commercial grade low density polyethylene (LDPE) resin. The resins were characterized for their rheological behavior in both shear and uniaxial extension. The polymers were extruded from a capillary under isothermal conditions and the extrudates were observed on-line using a video camera. ALE simulations were performed using molecular constitutive model like eXtended Pom-Pom (XPP) for branched (LDPE). The simulated extrudate swell was a good match with the experimental data. It was found that the swell values of LPDE through planar die are higher than the axisymmetric die.
Keywords: ALE-FEM; extrudate swell; polymer flow simulations; XPP

Rapid self-healing hydrogels - Phadke, Ameya; Zhang, Chao; Arman, Bedri; Hsu, Cheng-Chih; Mashelkar, Raghunath Anant; Lele, Ashish K.; Tauber, Michael J.; Arya, Gaurav; Varghese, Shyni (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Synthetic materials that are capable of autonomous healing upon damage are being developed at a rapid pace because of their many potential applications. Despite these advancements, achieving self-healing in permanently cross-linked hydrogels has remained elusive because of the presence of water and irreversible cross-links. Here, we demonstrate that permanently cross-linked hydrogels can be engineered to exhibit self-healing in an aqueous environment. We achieve this feature by arming the hydrogel network with flexible-pendant side chains carrying an optimal balance of hydrophilic and hydrophobic moieties that allows the side chains to mediate hydrogen bonds across the hydrogel interfaces with minimal steric hindrance and hydrophobic collapse. The self-healing reported here is rapid, occurring within seconds of the insertion of a crack into the hydrogel or juxtaposition of two separate hydrogel pieces. The healing is reversible and can be switched on and off via changes in pH, allowing external control over the healing process. Moreover, the hydrogels can sustain multiple cycles of healing and separation without compromising their mechanical properties and healing kinetics. Beyond revealing how secondary interactions could be harnessed to introduce new functions to chemically crosslinked polymeric systems, we also demonstrate various potential applications of such easy-to-synthesize, smart, self-healing hydrogels.
Keywords: adhesives; biomimetic materials; Hydrophobicity; molecular dynamics; smart materials

Ascertaining universal features of yielding of soft materials - Kamble, Samruddhi; Pandey, Anurag; Rastogi, Sanjay; Lele, Ashish K. (Rheologica Acta, 2013)
Many metastable complex fluids, when subjected to oscillatory shear flow of increasing strain amplitude at constant frequency, are known to show a characteristic nonlinear rheological response which consists of a monotonic decrease in the elastic modulus and a nonmonotonic change in the loss modulus. In particular, the loss modulus increases from its low strain value, crosses the elastic modulus, and then decreases with further increase in the strain amplitude. Miyazaki et al. (Europhys Lett 75:915-921, 2006) proposed a qualitative argument to explain the origin of the nonmonotonic nature of the loss modulus and suggested that in fact this response could be universal to all complex fluids if they are probed in a certain frequency window in which the fluid is dominantly elastic in the small strain limit. In this letter, we confirm their hypothesis by showing that a wide variety of complex fluids, irrespective of their thermodynamic state under quiescent conditions, indeed show the aforementioned characteristic nonlinear response. We also show that the maximum relative dissipation during yielding occurs when the imposed frequency resonates with the characteristic beta relaxation frequency of the fluid.
Keywords: Colloidal suspensions; Entangled melts; Gels; Glasses; Microgels; Rheology; Yielding

Necking in extrusion film casting: the role of macromolecular architecture - Pol, Harshawardhan V.; Thete, Sumeet Suresh; Doshi, Pankaj; Lele, Ashish K. (Journal of Rheology, 2013)
Extrusion film casting (EFC) is used on an industrial scale to produce several thousand tons of polymer films and coatings. While significant research has been carried out on necking of films of viscoelastic melts in EFC, the influence of macromolecular chain architecture on the necking behavior is not yet fully understood. In the present research, we have explored experimentally and theoretically the effects of long chain branching and molecular weight distribution on the extent of necking during EFC. Polyethylenes of essentially linear architecture but having narrow and broad molecular weight distributions, and polyethylenes having long chain branching were used for experimental studies. The EFC process was analyzed using the one-dimensional flow model of Silagy et al. [Polym. Eng. Sci. 36(21), 2614-2625 (1996)] in which multimode molecular constitutive equations namely the ``extended pom-pom'' equation (for long chain branched polymer melts) and the ``Rolie-Poly (Rouse linear entangled polymers)'' equation (for linear polymer melts) were incorporated. We show that the model qualitatively captures the salient features of the experimental data thereby elucidating the role of chain architecture on the extent of necking. (C) 2013 The Society of Rheology. [http://dx.doi.org/10.1122/1.4788911]

Rheology and microstructural studies of regenerated silk fibroin solutions - Nisal, Anuya; Kalelkar, Chirag; Bellare, Jayesh R.; Lele, Ashish K. (Rheologica Acta, 2013)
Regenerated silk fibroin solutions (RSF) are produced by dissolving degummed silk fibers in water. We have observed that RSF solutions at a concentration less than 15 % by weight exhibit an unusual gel-like response in conventional shear rheology measurements. At higher concentrations, the response is predominantly viscous (or liquid-like). We have probed this counterintuitive behavior of silk fibroin solutions by using microrheology, and interfacial rheometry. Scattering techniques were also used to understand the microstructure of RSF solutions as a function of the concentration. Our studies suggest that the gel-like response of the RSF solution may result from the formation of an interfacial film at the air-solution interface, which dominates the bulk rheological response.
Keywords: Interfacial rheology; Microrheology; Rheology; Silk

Nonisothermal analysis of extrusion film casting process using molecular constitutive equations - Pol, Harshawardhan; Banik, Sourya; Azad, Lal Busher; Thete, Sumeet Suresh; Doshi, Pankaj; Lele, Ashish K. (Rheologica Acta, 2014)
Extrusion film casting (EFC) is a commercially important process that is used to produce several thousand tons of polymer films and coatings. In a recent work, we demonstrated the influence of polymer chain architecture on the extent of necking in an isothermal film casting operation (Pol et al., J Rheol 57:559-583, 2013). In the present research, we have explored experimentally and theoretically the effects of long-chain branching on the extent of necking during nonisothermal film casting conditions. Polyethylenes of linear and long-chain branched architectures were used for experimental studies. The EFC process was analyzed using the 1-D flow model of Silagy et al. (Polym Eng Sci 36:2614-2625, 1996) in which the energy equation was introduced to model nonisothermal effects, and two multimode constitutive equations, namely the ``extended pom-pom'' (XPP, for long-chain branched polymer melts) equation and the ``Rolie-Poly stretch version'' (RP-S, for linear polymer melts) equation, were incorporated to account for the effects of polymer chain architecture. We show that the model does a better job of capturing the qualitative features of the experimental data, thereby elucidating the role of chain architecture and nonisothermal conditions on the extent of necking.
Keywords: Branched; Extrusion; Film; Linear; Necking; Nonisothermal; Polyethylene

Uptake of Azo dyes into silk glands for production of colored silk cocoons using a green feeding approach - Nisal, Anuya; Trivedy, Kanika; Mohammad, Hasan; Panneri, Suyana; Sen Gupta, Sayam; Lele, Ashish K.; Manchala, Ramesh; Kumar, Nirmal S.; Gadgil, Mugdha; Khandelwal, Harish B.; More, Snehal; Laxman, Ryali Seeta (ACS Sustainable Chemistry & Engineering, 2014)
Dyeing of textile fabrics is considered to be one of the most polluting industries today, and there is a need to develop green processes that can reduce this pollution. A promising technology that can potentially cleanup the dyeing of silk fibers that are widely used for textile applications would involve the generation of intrinsically colored silk cocoons. This can be achieved by feeding of Bombyx mori silkworm larvae with a modified feed of mulberry leaves containing a sprayed dye solution. This process significantly reduces the need for treating toxic dye effluents that are generated in traditional dyeing processes. In this report, we have evaluated a set of seven different azo dyes that are used in the textile industry for dyeing to produce intrinsically dyed silk. The dyes used in the study had similar chemical structures with systematically varying partition coefficients. The results suggest that while some dyes produced intrinsically colored silk other did not. Careful evaluation of the physical properties of these related azo dyes suggest that the balance of hydrophobic and hydrophilic character is necessary for diffusion of the dye from the alimentary canal of the silkworm larva into the hemolymph and later into the silk glands. The partition coefficient of the dye also determines the preferential association of the dye with either sericin or fibroin protein in the silkworm gland and finally into the cocoon. These insights are extremely important in development of novel dye molecules that can be successfully fed to Bombyx mori silkworm larvae for producing intrinsically colored silk of various colors and shades.
Keywords: Azo dyes; Biochemical pathways; Color silk; Dye uptake; `' Green `' silk

Extrusion film casting of long chain branched polypropylene - Chikhalikar, Kalyani; Banik, Sourya; Azad, Lal Busher; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Kulkarni, Surendra; Gupta, Surendra; Doshi, Pankaj; Pol, Harshawardhan; Lele, Ashish K. (Polymer Engineering and Science, 2015)
Extrusion film casting (EFC) is an important melt processing operation which is extensively used to make polypropylene (PP) films. Linear PP shows significant amount of necking and draw resonance during EFC. One of the ways to reduce necking is to introduce long chain branches (LCB) on the polymer backbone. The long branches impart extensional strain hardening behavior thereby stabilizing the melt flow. In this work, we investigate the influence of long chain branching in polypropylene on the extent of necking in the EFC process. Laboratory scale EFC experiments were performed on homopolymer PP of linear and long chain branched architectures. Simulations of the EFC process were carried out using the one-dimensional flow model of Silagy et al., Polym. Eng. Sci.,36, 2614 (1996) into which we incorporate two different multi-mode molecular constitutive equations namely, the eXtended Pom-Pom' equation (XPP, for long chain branched PP) and the Rolie-Poly' equation (RP-S, for linear PP). Our experimental data confirm that presence of long chain branching in PP reduces the extent of necking and our numerical predictions show qualitative agreement with experimental data, thereby elucidating the role of chain architecture on the extent of necking. POLYM. ENG. SCI., 55:1977-1987, 2015. (c) 2014 Society of Plastics Engineers

Insights into the molecular dynamics in polysulfone polymers from C-13 solid-state NMR experiments - Eldho, Kavalakal Mathai; Rajamohanan, P. R.; Anto, Ralf; Bulakh, Neelima N.; Lele, Ashish K.; Ajithkumar, Thalasseril G. (Journal of Physical Chemistry B, 2015)
The molecular and segmental motions in three different grades of ductile polysulfone polymers; poly(ether sulfone) (PESU), polysulfone (PSU), and poly(phenyl sulfone) (PPSU) are probed using C-13 solid-state NMR experiments. Polarization inversion spin exchange at magic angle (PISEMA) experiments indicates that the phenyl rings in the polymers are undergoing pi-flip motions on the order of 100 kHz. The temperature dependent PISEMA experiments show that the fraction of mobile regions that undergoes aromatic pi-flips is higher in PPSU than in the other two polymers. The center band only detection of exchange (CODEX) experiments was carried out and was unable to detect any slow segmental motions in the chains. A combination of C-13 spin-lattice relaxation time (T-1) and T-1-filtered PISEMA experiments show that the mobile regions in all the polymers are dynamically heterogeneous.

Long chain branched impact copolymer of polypropylene: microstructure and rheology - Chikhalikar, Kalyani; Deshpande, Anushree; Pol, Harshawardhan; Dhoble, Deepa Arun; Jha, Saroj; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Kulkarni, Surendra; Gupta, Surendra; Lele, Ashish K. (Polymer Engineering and Science, 2015)
A biphasic impact copolymer of polypropylene (ICP) was modified with peroxide by reactive extrusion process resulting in reduced melt flow index, improved melt strength, and higher die swell. The polymers were for the first time subjected to systematic rheological and microstructural characterization in an effort to understand their structure-property relations. In shear rheological tests, the modified ICP displayed higher flow activation energy, reduced values of loss tangent and nearly equal frequency dependence of storage and loss modulli. The modified ICP also showed strain hardening behaviour in uniaxial extensional rheology and higher crystallization temperature in differential scanning calorimetry (DSC). All these are definitive indications of the presence of long chain branches (LCB). Fitting the rheological data of modified ICPs with the eXtended Pom Pom (XPP) model indicated the presence of LCB on the higher molecular weight fraction in the polymer, a result which was corroborated with multi-detector high temperature gel permeation chromatography (HT-GPC). More importantly, the matrix and rubber phases of the ICP were separately characterized for presence of long chain branching by rheology, DSC and HT-GPC. The results indicate that while LCB existed in the matrix phase, microgels were present in both phases indicating that the reaction with peroxide occurred in both phases. POLYM. ENG. SCI., 55:1463-1474, 2015. (c) 2014 Society of Plastics Engineers

Porous poly(ethylene glycol)-polyurethane hydrogels as potential biomaterials - Divakaran, Anumon V.; Torris, Arun A. T.; Lele, Ashish K.; Badiger, Manohar V. (Polymer International, 2015)
We report the synthesis of porous poly(ethylene glycol)-polyurethane (PEG-PU) hydrogels using PEG-4000 as a soft segment and 4,4-methylenebis(cyclohexylisocyanate) as a hard segment. The degree of swelling in the hydrogels could be controlled by varying the amount of crosslinking agent, namely 1,2,6-hexanetriol. Structural characterization of the hydrogels was performed using solid-state C-13 NMR and Fourier transform infrared spectroscopy. Wide-angle X-ray diffraction studies revealed the existence of crystalline domains of PEG and small-angle X-ray scattering studies showed the presence of lamellar microstructures. For generating a porous structure in the hydrogels, cryogenic treatment with lyophilization was used. Scanning electron microscopy and three-dimensional micro-computed tomography imaging of the hydrogels indicated the presence of interconnected pores. The mechanical strength of the hydrogels and xerogels was measured using dynamic mechanical analysis. The observed dynamic storage moduli (E) for the equilibrium swollen and dry gels were found to be 0.15 and 4.2 MPa, respectively. Interestingly, the porous PEG-PU xerogel also showed E of 5.6 MPa indicating a similar mechanical strength upon incorporating porosity into the gel matrix. Finally, preliminary cytocompatibility studies showed the ability of cells to proliferate in the hydrogels. These gels show promise for applications as scaffolds and implants in tissue engineering. (c) 2014 Society of Chemical Industry
Keywords: hydrogels; permeability; poly(ethylene glycol); polyurethane; porosity

Star telechelic poly(L-lactide) ionomers - Kulkarni, Amruta; Lele, Ashish K.; Sivaram, Swaminathan; Rajamohanan, P. R.; Velankar, Sachin; Chatterji, Apratim (Macromolecules, 2015)
Poly(L-lactide) (PLA), a biodegradable and biorenewable polymer, has many excellent properties that are equivalent to those of petroleum-derived plastics such as polystyrene, aromatic polyesters, etc. However, a major disadvantage of PLA which limits its processability is its poor melt elasticity. In this work we explore the possibility of improving the viscoelastic properties of PLA melt by incorporating ionic groups on the polymer. Specifically, we demonstrate the synthesis of star telechelic PLA anionomers by a three-step procedure involving synthesis of Star PIA, converting the hydroxyl end groups into carboxylic acid end groups, and finally converting these into ionic groups. Rheology data showed a dramatic increase in the elasticity of the star telechelic ionomer melts relative to the Star PLA melts. The viscoelasticity of star telechelic ionomers melts could be modulated by varying the number of ionic groups per molecule.

Effect of plug temperature on the strain and thickness distribution ofcomponents made by plug assist thermoforming - Marathe, D.; Rokade, D.; Azad, Lal Busher; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Gupta, S.; Kulkarni, S.; Juvekar, Vinay A.; Lele, Ashish K. (International Polymer Processing, 2016)
Plug temperature is a key parameter affecting the thickness distribution of thermoplastic components made by plug assist thermoforming. For a specified pair of plug and plastic sheet, the variation in plug temperature can alter the coefficient of friction (COF) between the pair. We show here how the temperature dependence of COF influences the nature and extent of biaxial stretching of the sheet and consequently the thickness distribution of the thermoformed component. In the present study, high impact polystyrene (HIPS) sheets were thermoformed into axisymmetric cups using a plug-assist process in which the aluminum plug temperature (T-plug) was varied from ambient to above the glass transition temperature of HIPS (similar to 100 degrees C). Biaxial strain maps on the surfaces of the formed cups were measured and quantified using Grid Strain Analysis (GSA). Thickness distributions of the cups were also measured. Temperature dependent COF between HIPS and aluminum was determined independently using a rotational rheometer. The measured COF was low for T < 100 degrees C, whereas it increased appreciably at and above 100 degrees C. We conclude that when T-plug < 100 degrees C the HIPS sheet slips on the plug during forming, and this results in biaxial stretching of the base and walls of the formed cup. In contrast for T-plug > 100 degrees C, a significant reduction in the magnitude of slip is expected. Here the sheet is gripped at the clamp and by the plug during forming which causes reduced biaxial stretching of the base and increased uniaxial stretching of the walls of the cup. Simulations of plug-assist thermoforming using a temperature dependent COF showed qualitative agreement with the GSA data thereby supporting our inferences.

Thermo-reversible sol-gel transition of aqueous solutions of patchy polymers - Parmar, Indravadan A.; Shedge, Aarti S.; Badiger, Manohar V.; Wadgaonkar, Prakash P.; Lele, Ashish K. (RSC Advances, 2017)
While aqueous solutions of several amphiphilic thermo-reversible polymers show gelation upon heating, there are fewer examples of polymer solutions that exhibit gelation when cooled. This paper reports an interesting phenomenon of abrupt thermoreversible gelation of aqueous solutions of a hydrophobically modified polymer upon cooling. A high molecular weight precursor copolymer (PCP, (M-w) over bar approximate to 5 x 10(6) g mol(-1)) of N, N-dimethylacrylamide (70 mol%) and acrylic acid (30 mol%) was modified by reacting 10 mol% of the acrylic acid groups with n-dodecyl amine to form a hydrophobically modified copolymer (HMCP). The composition of the copolymer was ascertained using NMR spectroscopy. Cooling the solution of PCP at a controlled rate resulted in a gradual increase in its low shear viscosity as dictated by the flow activation energy. In contrast, cooling the solution of HMCP under identical conditions resulted in an abrupt and large non-Arrhenius increase in viscosity at a specific transition temperature, which decreased with decrease in polymer concentration. Fluorescence measurements and dynamic light scattering data showed that abrupt gelation happened upon cooling, when polymer coils percolate accompanied with concomitant transition in chain conformation from compact micellar coils formed by intra-chain hydrophobic associations to swollen polymer coils connected by inter-chain hydrophobic interactions.

Analytical solutions of an isothermal two-dimensional model of a cathode flow channel in a proton exchange membrane fuel cell - Thosar, Aniket U.; Lele, Ashish K. (Chemical Engineering Science, 2018)
Two key assumptions are usually made while deriving analytical solutions of coupled kinetics and transport equations in a single channel on the cathode plate of a proton exchange membrane fuel cell (PEMFC). These are: plug flow and uniform oxygen concentration along the depth of the channel. However these assumptions are not always valid under typical operating conditions of a PEMFC, and particularly so at high current density. In this article we relax these two assumptions and present approximate analytical solutions of the governing equations using the methodology of separation of variables followed by power series solution. Spatial profiles of oxygen concentration and current density were derived, which led to the final derivation of a comprehensive current-potential relationship (polarization curve) in the reaction-controlled regime of an operational PEMFC. We compare polarization curves predicted by the present model with predictions of the earlier analytical model and also with a complete 3D-simulation of the same flow geometry and operation conditions. The local profiles of oxygen concentration and the polarization curve predicted by the present model compare far better with the 3D simulations than the earlier analytical model. While this comparison highlights the importance of the effects of finite oxygen diffusion rate and velocity profile in the channel on the polarization curves, it also points to other important factors that affect the current-potential relation.

Judicious reduction of supported Ti catalyst enables access to disentangled ultrahigh molecular weight polyethylene - Gote, Ravindra P.; Mandal, Dipa; Patel, Ketan; Chaudhuri, Krishnaroop; Vinod, C. P.; Lele, Ashish K.; Chikkali, Samir H. (Macromolecules, 2018)
Heterogeneous Ziegler-Natta and homogeneous metallocene catalysts are known to produce ultrahigh molecular weight polyethylene (UHMWPE) in the entangled state. On the other hand, only (two) homogeneous single-site catalysts are reported to yield disentangled UHMWPE (dis-UHMWPE). This disparity between the two types of catalysts and the two states of polyethylene can be bridged if a heterogeneous single-site catalyst that can yield dis-UHMWPE is made accessible. Here, one-pot two-step synthesis of a MgCl2 supported [Ti(OEt)(4)] derived catalyst 1 with a two-stage activation strategy is reported to produce dis-UHMWPE. Second activation of catalyst 1 was performed by adding excess modified methylaluminoxane (MMAO12), and XPS analysis indicated that the catalyst existed in only Ti(III) state at [A1]/[Ti] ratio of 600. Catalyst 1 after second activation with MMAO12 was found to be highly active in ethylene polymerization and produced dis-UHMWPE. Polymerization conditions were tailored to obtain molecular weight (M-w) as high as 13 million g/mol PE. To the best of our knowledge, this is the first time a heterogeneous catalyst (catalyst 1) that displays pseudosingle site nature is able to produce dis-UHMWPE. The thus-prepared nascent polyethylene revealed a melting temperature of 141-144 degrees C, which is a characteristic melting transition for a dis-UHMVVPE. The disentangled state of the nascent PE and its M-w and MVVD were further authenticated by rheological investigations. Isothermal time, sweep oscillatory experiments in linear viscoelastic limit revealed a rapid rise in elastic modulus followed by equilibration to plateau modulus, which are characteristic features of the disentangled state. Thus, a pseudo-singlesite heterogeneous catalyst has been accessed, which upon second activation with excess MMAO12 led to the production of dis-UHMWPE.

Analytical solutions of an isothermal two-dimensional model of a cathode flow channel in transport limited operational regimes of a proton exchange membrane fuel cell - Thosar, Aniket U.; Lele, Ashish K. (Chemical Engineering Science, 2019)
In the quest for obtaining accurate closed-form analytical expressions for polarization curve of a proton exchange membrane fuel cell (PEMFC), we have recently presented a two-dimensional model that accounts for oxygen concentration gradient and velocity gradient along the depth of a cathode flow channel. The model was developed for the case when Tafel kinetics of oxygen reduction reaction (ORR) on the cathode governs the overall rate of oxygen consumption. An improved match between predictions of the model and full three-dimensional simulations was obtained over the entire range of current density compared with earlier models which assumed homogenous oxygen concentration in the channel depth and plug flow velocity profile. In reality however, ORR kinetics is often not the rate limiting step for oxygen consumption in the cathode catalyst layer (CCL) at high current density since the Tafel kinetics is modulated by transport resistances in the CCL. In this article, we extend our two-dimensional analytical model to two different transport-limited regimes of CCL operation namely, slow oxygen transport across the CCL and slow proton transport across the CCL. We compare model predictions with results of full three-dimensional simulations in both cases and show that they are in excellent agreement even in these transport limited operational regimes of PEMFC. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Analytical modelling; Polarization curve; Proton exchange membrane fuel cells; Transport resistance

Comprehensive analytical model for polarization curve of a PEM fuel cell and experimental validation - Thosar, Aniket U.; Agarwal, Harshal; Govarthan, S.; Lele, Ashish K. (Chemical Engineering Science, 2019)
The kinetics of cathodic oxygen reduction reaction (ORR) in a proton exchange membrane fuel cell (PEMFC) is significantly modulated by the resistances for transport of reactants to the catalytic sites offered by different components of the fuel cell. This modulation governs the polarization curve of the PEMFC. Consequently, the various operating, geometric and material parameters of the fuel cell dictate the polarization curve. The effects of these parameters on the polarization curve over the entire range of current density, from zero to limiting current, can be predicted using detailed numerical simulations, which are however expensive. Analytical models, although simple can capture the essential details of physico-chemical processes occurring inside a PEMFC and are significantly inexpensive. In this article, we derive an analytical equation of the polarization curve which is valid over the entire range of current density. Specifically, the representative situation of a humidified low temperature PEMFC is considered wherein oxygen transport resistance in the cathode catalyst layer (CCL) is encountered at lower current density than proton transport resistance in the CCL. A novel experimental methodology is illustrated to confirm that this is indeed the case. Next, we elucidate a procedure to determine in-situ oxygen diffusion coefficients in the various domains of an operational PEMFC. Finally, it is shown that the analytical polarization curve predicted using these parameters is in excellent agreement with the experimental and numerically simulated polarization curves over the entire range of current density. The significance of this work is that the analytical model relates the performance of a PEMFC to all operating and geometric parameters as well as the average transport and kinetic properties of the materials used in its different components, without the need for computationally expensive numerical simulations. The model can therefore provide useful insights for enhancing the performance of PEMFC in different regimes of current density as well as for diagnostic purposes. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Fuel cell equation; Modelling; PEMFC; Polarization curve

Enhancing thermomechanical and chemical stability of polymer electrolyte membranes using polydopamine coated nanocellulose - Ram, Farsa; Velayutham, Parthiban; Sahu, Akhila Kumar; Lele, Ashish K.; Shanmuganathan, Kadhiravan (ACS Applied Energy Materials, 2020)
We report here an approach to enhance the chemical and thermomechanical stability of polymer electrolyte membranes without compromising proton conductivity. Multifunctional polydopamine coated nanocellulose (PNC) was prepared by oxidative polymerization of dopamine on nano cellulose fibers and subsequently incorporated in Nafion by solution blending. PNC had a very significant effect on the thermomechanical properties of Nafion showing up to 200% improvement in the storage modulus at 90 degrees C. The PNC network also enhanced the dimensional stability of Nafion under constant stress. The 3 wt % PNC composite membrane showed a drastic reduction in creep compliance of about 39.9% and 46.5% in J(max) at 30 degrees and 60 degrees C, respectively. Free radical scavenging properties of polydopamine also helped to significantly enhance the chemical stability of Nafion, which was ascertained by accelerated degradation tests conducted in Fenton's reagent at 70 degrees C over 40 days. F-19 CP MAS solid state NMR, FTIR, and tensile tests on the membranes show higher chemical stability of the 3 wt % PNC composite membrane. The proton conductivity of the 3 wt % PNC composite membrane at 90 degrees C and 100% RH (similar to 125 mS/cm) was slightly higher than the Nafion membrane (similar to 94 mS/cm) at similar conditions. The retention of proton conductivity even with lower water uptake could be ascribed to proton hopping through polydopamine coated nanocellulose. Performance of the composite membrane was also evaluated in a single stack fuel cell and found to be better than recast Nafion. The benefits derived by this approach are not restricted to Nafion alone and shall broadly apply to many other polymer membranes.
Keywords: cellulose nanofibers; chemical stability; dimensional stability; fuel cell; polydopamine; polymer electrolyte membrane

Microstructure and yielding of capillary force induced gel - Huprikar, Sameer; Usgaonkar, Saurabh; Lele, Ashish K.; Orpe, Ashish V. (Rheologica Acta, 2020)
We have investigated the rheology and structure of a gel formed from a mixture of non-Brownian particles and two immiscible liquids. The suspension of particles in a liquid undergoes gelation upon the addition of a small content of second, wetting liquid which forms liquid bridges between particles leading to a sample spanning network. The rheology of this gel primarily exhibits a yield stress at low shear rates followed by a linear variation of shear stress at high shear rates. The apparent yield stress extracted from the flow curves increases rapidly with volume fraction of the second liquid before saturation, while it exhibits a monotonic increase with increasing particle concentration. Rescaling of the yield stress curves using suitable shift factors results in an empirical expression for the yield stress showing squared dependence on liquid fraction and a rapid increase with particle fraction above a certain value, both combined in a highly non-linear manner. The microstructural variations with changing secondary liquid content and particle fractions are captured using three-dimensional X-ray tomography technique. The microstructure is observed to show increased local compactness with increased liquid content and increased spatial homogeneity with increased particle fractions. The images from X-ray tomography are analysed to obtain the distributions of particle-particle bonds (coordination number) in the system which serve to explain the observed yield stress behaviour in a qualitative manner.
Keywords: Capillary force; Flow curve; gel; Microstructure; Rheology; Yield stress

Rheological quantification of the extent of dissolution of ultrahigh molecular weight polyethylene in melt-compounded blends with high density polyethylene - Chaudhuri, Krishnaroop; Lele, Ashish K. (Journal of Rheology, 2020)
Melt compounding of ultrahigh molecular weight polyethylene (UHMWPE) with high density polyethylene (HDPE) promises to be an alternative route to prepare bimodal polyethylene grades. However, complete dissolution of UHMWPE in HDPE cannot be guaranteed during melt compounding. Indeed, in an earlier work [K. Chaudhuri et al., Polym. Eng. Sci. 59, 821-829 (2019)], it was shown that a fully entangled UHMWPE did not mix well with commercial HDPE. However, a disentangled UHMWPE (dPE) could be melt-mixed in the same HDPE as evidenced qualitatively by rheological measurements. The present work is focused on quantifying the extent of dissolution of dPE in HDPE. The proposed method involves fitting rheological models for linear viscoelasticity of entangled bimodal blends of polydisperse polymers to dynamic oscillatory shear data and extracting information on the extent of dissolved species. The time-dependent diffusion model of des Cloizeaux is used along with the theory of double reptation (DR) to describe the dynamics of polydisperse homopolymers and also to extract the molecular weight distribution of the UHMWPE sample. A quadratic mixing rule, consistent with the DR model, is used to describe the dynamics of bimodal blends. Melt-mixed dPE/HDPE blends were prepared and characterized for their linear viscoelastic response by frequency sweep tests. The blends showed complex behavior with multiple crossover points, especially for the higher content of dPE. The bimodal model was then fit to the experimental frequency sweep data to determine the only unknown parameter, namely, the extent of dissolved dPE. It was found that a considerable fraction of dPE is dissolved in HDPE during melt compounding.
Keywords: blends; Disentangled UHMWPE; double reptation; HDPE; Mathematical modeling

Interdigitated flow field impact on mass transport and electrochemical reaction in high-temperature polymer electrolyte fuel cell - Agarwal, Harshal; Thosar, Aniket U.; Bhat, Santoshkumar D.; Lele, Ashish K. (Journal of Power Sources, 2022)
The enhanced performance of Polybenzimidazole (PBI) based high-temperature polymer electrolyte fuel cell (HT-PEFC) with interdigitated flow field over the other flow fields can be a consequence of higher average pressure developed on the flow field due to dead end in the channels or faster mass transport due to pressuredriven convection in the gas diffusion layer (GDL). In the present study, the effect of average pressure on the flow field and mass transport mechanism in the GDL on the HT-PEFC performance have been systematically decoupled. Three-dimensional simulation validated by experimental studies confirm that the enhanced performance in case of the interdigitated flow field is due to faster mass transport in the GDL and not due to higher average gas pressure. The simulation studies are performed on the interdigitated flow field and compared against the parallel flow field to have an insight into the effect of key operating and geometric parameters. There exists an optimum value for channel to rib ratio and current density saturates after an air stoichiometry of 4 which is validated by experiments.
Keywords: HT-PEFC; Interdigitated flow field; Mass transport mechanism; pressure; stoichiometry

Optimization of Liquid Organic Hydrogen Carrier (LOHC) dehydrogenation system - Rao, Nihal; Lele, Ashish K.; Patwardhan, Ashwin W. (International Journal of Hydrogen Energy, 2022)
In this paper, the perhydrodibenzyltoluene dehydrogenation flowsheet has been simulated. Modelling of the dehydrogenation reactor has been performed using the 1-D model. External and internal mass transfer resistances are also considered. Non-isothermal pellet condition has been considered for simulating the dehydrogenation reactor. The flowsheet simulation has been carried out in DW-Sim v 6.5.2 integrated with the reactor model coded in Python. NET. The dehydrogenation reactor is operated at a feed temperature between 523 K -613 K, a wall temperature of 623 K and 653 K, and a reactor pressure maintained at 1.2 atm. The amount of catalyst required for the perhydrodibenzyltoluene (PDBT) dehy-drogenation reactor is evaluated such that the conversion reaches 99%. The process flowsheet has been simulated to produce 10 Nm(3)/hr of industrial-grade hydrogen. The effects of feed temperature, wall temperature, and hydrogen burner efficiency on various system requirements, including catalyst weight, energy supplied to the dehydrogenation reactor, areas of the heat exchanger, and hydrogen production from the reactor, have been discussed. Preliminary cost optimization based on the heat exchangers and catalyst at various feed temperatures, reactor wall temperature, and hydrogen burner efficiency has been carried out. (C) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Dehydrogenation; DWSim; LOHC; Perhydrodibenzyltoluene; Python; simulation

ABPBI-based hollow fiber membranes for forward osmosis (FO) possessing low reverse salt flux - Thorat, Nitin M.; Lele, Ashish K.; Kharul, Ulhas K. (Desalination and Water Treatment, 2024)
The poly(2,5-Benzimidazole), known for its excellent thermochemical stability, was evaluated as a membrane material for forward osmosis. The dope in methane sulfonic acid was used to make hollow fiber membranes. The availability of bound MSA in HFMs was compared with its neutral form. Aqueous solutions of two common salts reported for FO (NaCl and MgCl2) were used as a draw solution at varying concentrations. The performance was determined in terms of water flux and reverse salt flux. The long-term performance of the membrane was assessed. The heat pretreatment of membranes was beneficial in offering low reverse salt flux, a crucial parameter in FO. The heat treatment at 350 degrees C exhibited excellent performance of low-RSF, irrespective of the draw solute used. The presence of MSA in the membrane matrix was found to be beneficial. Present HFMs exhibited reverse salt flux as low as 0.003 mol m-2 h-1 using 2 mol L-1 MgCl2 as a draw solution. The water flux of present membranes was lower than that of reported FO-membranes, which is attributable to the larger thickness of the present membranes. The findings will be used to make ABPBI-based membranes in thin form to elevate the fluxes and their practical applicability.
Keywords: ABPBI; Forward osmosis; Hollow fiber membrane; Low reverse salt flux

Linear poly(lactic acid) ionomers with pendant ionic groups - Joseph, Seena; Menon, Abhijith Hari; Lele, Ashish K.; Chikkali, Samir H. (New Journal of Chemistry, 2024)
Although PLA is widely used, melt processing of this polymer is still a challenging task. In our efforts to improve the melt strength and processability of PLA, we report the synthesis of high molecular weight linear PLA ionomers. PLA copolymers (CP1-CP3) with pendant alkyne groups were synthesized by reacting L-lactide with propargylated lactide. The existence of copolymers with alkyne groups was unambiguously demonstrated, and the percentage of alkyne was found to be 3-7%. A click reaction protocol was developed to treat the resultant alkyne functionalized copolymers (CP1-CP3) with mercaptosuccinic acid (MSA) and pendant carboxylic acid group functionalized copolymers (CP1-MSA1 to CP3-MSA3) were obtained. The 1-2D NMR confirmed the formation of a major MSA bis-addition product, along with a minor mono-addition product. In the final step, the MSA functionalized copolymers were treated with sodium hydride (NaH) to obtain the corresponding linear PLA ionomers (CP1-MSA1-Na1 to CP3-MSA3-Na3). Significant improvement in thermal and melt rheological properties was observed in these ionomers, as compared to the precursor copolymer and unmodified PLA, due to the microstructural changes caused by the association of the ionic groups. Storage modulus (G `) and loss modulus (G `') values showed a substantial increase in melt elasticity of the ionomers with G ` > G `', whereas the unmodified PLA melt behaved like a viscoelastic liquid. Detailed investigation reveals that incorporating pendant ionic groups in a high molecular weight linear PLA remarkably enhances the elastic modulus from 10 to 100 000 Pa (four orders of magnitude).

Poly(2,5-Benzimidazole) as a membrane material for solvent dehydration: effect of bound methanesulfonic acid - Alladi, Lavanya; Lele, Ashish K.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2025)
Towards addressing issues of solvent stability of polymeric membrane materials for pervaporation (PV), this work investigates thermochemically robust poly(2,5-benzimidazole) (ABPBI) bound with methane sulfonic acid (MSA) for solvent dehydration, for the first time to our knowledge. Phase inversion membranes with and without bound-MSA were prepared, thermally treated at different temperatures up to 350 degrees C, and analyzed for physical and pervaporation properties. The physical characterizations (FTIR, WAXD, TGA, XPS, SEM, and EDX) and sorption analysis were performed using flat sheet membranes, whereas hollow fiber membranes were used for the pervaporation analysis with chosen solvents (alcohols and two polar aprotic solvents). Physical characterizations established the presence of MSA and the nonporous, dense nature of membranes, irrespective of their treatment temperatures. The sorption of pure solvents in the membrane is primarily affected by thermal treatment of the membranes. The pervaporation analysis was performed using different solvent: Water feed compositions. Using 85:15 as the feed, the average separation factors for dehydration of isopropanol, acetonitrile, and N,N-dimethylformamide (DMF) were 393, 213, and 185, respectively, with an appreciable ``pervaporation separation index.'' The long-term membrane performance till 360 h was analyzed to shed light on practical applicability.
Keywords: membranes; separation techniques; synthesis and processing techniques